2000
DOI: 10.1128/jvi.74.6.2793-2803.2000
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Two Related Viral Early Genes in Epstein-Barr Virus-Associated Tumors

Abstract: The transcription of two early "leftwardly" expressed genes carrying repetitive sequences, IR2 and IR4, has been studied for Epstein-Barr virus-associated tumors, and for established B-cell lines, using sequence-specific probes generated for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 41 publications
6
51
0
Order By: Relevance
“…Viral markers chosen for examination in this study (Figure 2 and legend) include the small EBV RNAs (EBERs 1 and 2) frequently used in searches for EBV (Labrecque et al, 1995;Brink et al, 2000), the EBV nuclear antigen, EBNA1, responsible for viral maintenance and found expressed in most or all virally associated tumours (IARC, 1997), and a variety of other genes associated with expression in NPC (Hitt et al, 1989;Xue et al, 2000), or associated with epithelial cell immortalisation in culture (Griffin and Karran, 1984;Karran et al, 1990) or, alternatively, thought to be B-cell specific (Xue et al, 2000.…”
Section: Expression Of Ebv Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…Viral markers chosen for examination in this study (Figure 2 and legend) include the small EBV RNAs (EBERs 1 and 2) frequently used in searches for EBV (Labrecque et al, 1995;Brink et al, 2000), the EBV nuclear antigen, EBNA1, responsible for viral maintenance and found expressed in most or all virally associated tumours (IARC, 1997), and a variety of other genes associated with expression in NPC (Hitt et al, 1989;Xue et al, 2000), or associated with epithelial cell immortalisation in culture (Griffin and Karran, 1984;Karran et al, 1990) or, alternatively, thought to be B-cell specific (Xue et al, 2000.…”
Section: Expression Of Ebv Genesmentioning
confidence: 99%
“…Whole-cell DNA taken from the 15 breast carcinoma biopsies, and controls, were examined for the presence of EBV DNA, using as viral marker an early gene, LF3, which contains the repetitive IR4 sequence, and is found expressed in many tumours, including NPCs and Burkitt's lymphomas (BLs) (Xue et al, 2000. The IR4 repeats are present in high copy numbers (ranging from 22 to 33) in different cells and tumours (Xue et al, 2003).…”
Section: Ebv Dna and Gene Expression In The Breast Tumoursmentioning
confidence: 99%
See 2 more Smart Citations
“…If one hypothesizes that an EBV protein might bind DNA near or at telomere sites and prevent their shortening, the question would be which of the viral proteins, within p31 DNA, might ful®l this role? Candidate genes may be found among those associated with the epithelial cell tumours, such as NPC (Hitt et al, 1989;Chen et al, 1992;Brink et al, 1998;Zhang et al, 1998;Hayes et al, 1999;Xue et al, 2000;Smith et al, 2000), see Figure 1. There is no suggestion in the literature (Strockbine et al, 1998) or in its structure (Baer et al, 1984), that BARF1, the only p31-containing viral function known to stimulate cell growth (Wei and Ooka, 1989;Wei et al, 1994Wei et al, , 1997, might act in this manner.…”
Section: Discussionmentioning
confidence: 99%